Biological and environmental monitoring of lead and exposure in the automobile industry - S.J Shah Taheri; A Rahimi Forooshani; A.R Koohpaii; M Dehghan Nasiri; F Golbabaii (Salāmat-i kār-i Īrān, 2012)
Background and Aims: Soldering is one of the most common activities in metal industries. Lead is used in soldering process and has considerable toxic effects. The aim of this study, therefore, was biological and environmental monitoring and investigating the effects of exposure to lead in soldering unit workers at an automobile industry.     Methods: In order to evaluate biological and environmental exposure to lead, a case-control study was accomplished on 60 workers in soldering unit (case group) and 60 workers in official unit (control group). Demographical and medical information were gained by a questionnaire. Blood samples were collected and analyzed using the NIOSH 8003 method and Atomic Absorption Spectroscopy (AAS) respectively and air samples were collected and analyzed using the NIOSH 7300 method and Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) respectively.     Results: The obtained results shown that, with the increasing of age and work experience, the blood lead level is also increased.(p=0.033)(p=0.003) In exposed group, the blood lead mean value was significantly higher than the control group (p-value<0.001). Prevalence of digestive, nervous, respiratory, dermal, kidney disorders, anemia diseases, and disorder in bone metabolism in exposed group were higher than the control group. The amount of lead level was negatively correlated with hemoglobin (r=-0.287;p=0.026) and hematocrit (r=-0.336;p=0.009) but There was no significant correlation between air and blood lead level.     Conclusion: The blood lead level may be increased in lead exposure due absence of personal protective equipment and poor personal hygiene. Increased lead level in blood can be resulted to various diseases and decrease in hemoglobin and hematocrit levels in blood.